2002
DOI: 10.1086/501962
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing and Antimicrobial Susceptibility of Vancomycin-ResistantEnterococcus faeciumin Brazil

Abstract: The results of our study indicate the occurrence of intra- and interhospital dissemination of VRE in Sao Paulo, Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0
3

Year Published

2004
2004
2009
2009

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 13 publications
2
13
0
3
Order By: Relevance
“…MLVA detected five main clusters of genetically related isolates from four Brazilian hospitals recovered during different periods. Persistence of enterococcal isolates sharing the same PFGE genotype and their intra-and interhospital spreading have also been described in previous investigations (1,10). In conclusion, MLVA accomplishes most of the desired typing features, including sufficient discriminatory power, speed, ease of use, and simple result interpretation.…”
supporting
confidence: 80%
“…MLVA detected five main clusters of genetically related isolates from four Brazilian hospitals recovered during different periods. Persistence of enterococcal isolates sharing the same PFGE genotype and their intra-and interhospital spreading have also been described in previous investigations (1,10). In conclusion, MLVA accomplishes most of the desired typing features, including sufficient discriminatory power, speed, ease of use, and simple result interpretation.…”
supporting
confidence: 80%
“…First described in 1988 in France and England (1,2), glycopeptide-resistant enterococci have been isolated in Brazil since 1996, when the first case of vancomycin-resistant enterococci (VRE) due to a Enterococcus faecium VanD 4 was reported in Curitiba (Paraná State) (3,4). Further VRE isolates (E. faecium with the vanA gene) were reported in São Paulo State (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the first case was reported in São Paulo [30]. Other cases occurred in different hospitals and, by 1998, VRE had spread throughout the country [31]. Disease severity controlled studies found that vancomycin resistance was predictive of increased mortality [32][33][34].…”
mentioning
confidence: 99%